High strength lightweight aggregate concrete using blended coarse lightweight aggregate origin from palm oil industry - Muhammad Aslam; Payam Shafigh; Mohd Zamin Jumaat (Penerbit Universiti Kebangsaan Malaysia, 2017)
The benefits of using structural lightweight concrete in construction industry, particularly in high rise buildings, over normal weight concrete are numerous. The main method of producing structural lightweight concrete is the use of lightweight aggregates instead of ordinary aggregates in concrete. Due to the limited resources for natural and artificial lightweight aggregates, the alternative sources for lightweight aggregates should be discovered from industrial wastes. Oil palm shell (OPS) and oil-palm-boiler clinker (OPBC) are two solid wastes from palm oil industry and are available in abundance in tropical regimes. The use of just OPS as coarse lightweight aggregate in concrete mixture has some drawbacks for concrete. The aim of this study was to investigate engineering properties of a lightweight concrete containing both of these aggregates. For this purpose, in this study, 50% (by volume) of OPS was replaced with OPBC in an OPS lightweight concrete. The test results showed that when OPS was substituted with OPBC, significant improvement was observed in the compressive, splitting tensile and flexural strengths. In addition, initial and final water absorption as well as drying shrinkage strain of blended coarse lightweight aggregate concrete were significantly less than OPS concrete.